The tack modifying effects of citrate compounds on hydroxypropylmethylcellulose solution / Nur Mariana Ayub - Ayub, Nur Mariana (2006)
The study sets to determine the effects of plasticizers on the tackiness of the hydroxypropylmethylcellulose (HPMC) solution. The HPMC solution, without or with the incorporation of plasticizers, was subjected to the tack measurement by using the torsion balance at 30°C. The plasticizers used were citric acid, triacetin, triethyl citrate and trisodium citrate. The blank HPMC and plasticizer loaded HPMC solution were subjected to molecular spectroscopy analysis by mean of Fourier Transform Infra-red Analysis. All plasticizers could modify the tack of 0.5% w/w HPMC solution. Nonetheless, none of the plasticizers could reduce the tack of HPMC solution to a value lower than that of the blank solution. The tack of plasticizer-added HPMC solution was mediated from the interaction between the polymer and/or plasticizer molecules, typically via the 0-H functional groups. Citric acid, triacetin, triethyl citrate and trisodium citrate could not effectively reduce the tack force of 0.5% w/w HPMC solutions.